Trends in Age Structure and Ageing Population in Nepal - Bhandari, Kamala (Journal of Population and Development, 2020)
The study attempts to examine the trend in the age structure of population and elderly population and its geographic and demographic variation in respect to the fedral structured country based on the census data. The study found noticeable changes in the age structure of the population in the country. The share of children is shrinking with growing proportions of older population aged 60 and above throughout the Nation. More than half of population falls in the 15-59 years category that conforms Nepal population is primarily young, which is also known as the 'youth bulge' or 'demographic dividends' and will shift into the category of 60 and above in a few decades. Hence the Nepal's population is gradually ageing over the years. The proportion of children and old aged population was observed higher in Mountain (38% and 8.8%)), rural area (38% and 8.8%) and working age population was in hill region (58%) and in urban area (59%) along with province 3. According to the 2011 population census, the proportion of population aged 60 and above is 8.1 percent, majority of them are in their sixties (69%) and observed same in all regions of the country. As measured by sex ratio in both rural and urban area female outnumber male and also reported the expectation of life is higher for female then male in this age group of the country. Among the 77 districts Gorkha (12.75%) reported the highest, and Jajarkot (5.12%), reported the lowest proportion of their population being old.